(untitled) (University Journal of Zoology, Rajshahi University, 2009)
A trial was conducted to evaluate the effects of combination of soybean meal (SBN), mustard oilcake (MOC), sesame oilcake (SOC) and linseed oilcake (LOC) as alternative for dietary fish meal (FM) protein for Labeo rohita fingerling for a period of 56 days. Six experimental diets were formulated by replacing 30, 50, 60, 70 and 100% (2 diets) of the total dietary fish meal protein by the combination of FM, SBM, MOC, SOC, and LOC. The combinations of the protein sources were as diet 1 (FM 100%), diet 2 (FM:SBM:MOC::70:15:15), diet 3 (FM:SBM:SOC:LOC::50:20:20:10), diet 4 (FM:SBM:SOC:LOC::40:20:20:20), diet 5 (FM:SBM:SOC:LOC::25:30:15:30), diet 6 (SBM:MOC:SOC:LOC::25:25:25:25) and diet 7 (SBM:SOC:LOC::40:30:30). The performances of these six test diets were compared with the diet 1 (control). All diets were iso-nitrogenous containing about 30% protein. The growth trial was conducted in a flow through system under laboratory condition with three replications for each treatment. On the basis of the growth response, food conversion ratio (FCR), protein efficiency ratio (PER) diet 7 showed better performance followed by diet 1, diet 2, diet 5, diet 3, diet 4 and diet 6 respectively but those were not significantly different (P>0.05). The diet 6 produced the lowest performance. The apparent protein digestibility (APD) values for all the experimental diets were very nearer but significantly different (P0.05) in diets even from control one which were formulated to evaluate the effects of combination of low cost oil seed cakes as dietary protein source for Labeo rohita fingerling. Hence, it might be concluded that from the economic point of view, that all the low cost oil seed cakes which are locally available can be used in combination form as the alternative protein source for the feed of Labeo rohita. Key words: Oil seed cakes, Labeo rohita, fingerling, protein source. Â doi:10.3329/ujzru.v27i0.1949 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 25-30